A new species of Tisbintra (Harpacticoida, Tisbidae), and range extension for Geehydrosoma brevipodum (Harpacticoida, Cletodidae) from northern Colombia - Samuel Gómez; Juan M. Fuentes-Reinés (Caldasia)
Water samples taken from the Rodadero Bay, Caribbean Colombian coast, yielded an undescribed species of harpacticoid copepod of the family Tisbidae, Tisbintra monroyi sp. nov. and a new record of Geehydrosoma brevipodum. The genus Tisbintra is composed of two species only, Tisbintra nankaurica known from Nicobar Islands (Bay of Bengal and Andaman Sea), and Tisbintra jonesi known from the Gulf of Mannar (southern India and western Sri Lanka) and the coast of Kenya. The new species can be separated from T. nankaurica and T. jonsei by the number of segments of the female and male antennule, relative length of the setae on the P5EXP, and the number of setae/spines in the female P6. The record of Tisbintra monroyi sp. nov. in Colombia is the first one of the genus outside the Indian Ocean. The new record of Geehydrosoma brevipodum, known previously from the Mexican Tropical Eastern Pacific, constitutes a range extension of the species to the Caribbean Colombian coast.